2017
DOI: 10.1007/s40258-017-0312-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Models in Breast Cancer Screening in the General Population: A Systematic Review

Abstract: State-transition modeling was the most frequently applied analytic approach. Different methods in modeling the progression of ductal carcinoma in situ to invasive cancer were identified because there is currently no agreement on the biological behavior of noninvasive breast cancer. Main weaknesses were the lack of precise utility estimates and insufficient reporting of validation. Sensitivity analyses of assumptions regarding ductal carcinoma in situ and in particular adequate validation are critical to minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 101 publications
0
19
0
1
Order By: Relevance
“…In situ carcinoma may or may not progress to invasive cancers. Schiller-Fruhwirth et al [ 53 ] identified the uncertainty about the biological relation between in situ and invasive cancers to be the root of the differences in modeling. However, treatment guidelines usually recommend treatment of in situ cancers [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In situ carcinoma may or may not progress to invasive cancers. Schiller-Fruhwirth et al [ 53 ] identified the uncertainty about the biological relation between in situ and invasive cancers to be the root of the differences in modeling. However, treatment guidelines usually recommend treatment of in situ cancers [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…being justified. The mean size of effect pooled from randomised controlled trials (RCTs) is 15-25%, 6,9,11,16,19,20,25,30,[33][34][35][36][37] from models/estimates is 11-33%, [33][34][35] and from observational/ population evidence is 28-56%. 9,25,36 The Cochrane review reported statistically non-significant all-cancer mortality reduction.…”
Section: Screening Mammographymentioning
confidence: 99%
“…Two systematic reviews (19,132) have previously explored the outcomes of economic evaluations relating to breast screening programmes. Schiller-Fruhwirth et al (19) reported on the lack of breast screening specific utilities and insufficient reporting of validation in their review of economic models.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The quality of the HSUVs applied is particularly pertinent in the appraisal of oncological interventions, where quality of life may have greater influence on QALYs than the modest gains in life expectancy (17). Many studies have evaluated the cost-effectiveness of breast cancer screening (18,19), with those including quality of life in their evaluation reporting fewer net benefits, yet few have commented on the quality of the utility estimates used to inform them. When deciding on preferred screening policy it is critical to be able to accurately value the options available to women of being able to attend routine screening (20).…”
Section: Introductionmentioning
confidence: 99%